Persepsi Pihak Industri Terhadap Kompetensi Mahasiswa PTM pada Program Magang Industri - Risa Tri Komala Sari; Yuyun Estriyanto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2024)
The purpose of this study was to determine the assessment of the industry, especially field supervisors regarding the competence of students who participated in the industrial internship program majoring in Mechanical Engineering Education FKIP UNS with a concentration in Production for the 2022 period. This study uses a descriptive method, which aims to collect, analyze, and present data that has a relationship with the problem under study. Data collection techniques using questionnaires and interviews. The results showed that the industry's perception of the competence of PTM students was in the very good category and was considered quite in accordance with industry needs, with work attitude as the most prominent aspect (82.5%). However, there is still room for improvement, especially in the aspects of practical skills (74.2%) and knowledge application (76.5%) in order to produce graduates who are better prepared to face the demands of the dynamic world of work. With good assessments, especially in the work attitude aspect, PTM graduates have good competitiveness potential in the job market, but need to continue to improve their practical skills and knowledge application abilities to maximize employment opportunities. Conducting Conduct an in-depth analysis of the gap between the competencies expected by industry and those possessed by students so that it can be the basis for recommendations for curriculum improvements that are more specific to the demands of the labor market and improve the work readiness of PTM graduates.